Maternal sudden death: A nationwide retrospective study. (9th October 2022) - Braund, Sophia; Leviel, Juliette; Morau, Estelle; Deneux‐Tharaux, Catherine; Verspyck, Eric; ,
Abstract: Objective: To determine the prevalence of maternal sudden death (MSD) and to compare the characteristics of death between women with explained and unexplained sudden death. Design: A national retrospective study in France. Population: Maternal deaths related to an unexpected sudden cardiac arrest were extracted from the French National Confidential Enquiry into Maternal Deaths database for 2007–2012. Methods: Maternal, pregnancy, sudden death characteristics and maternal investigations were compared between women with explained and unexplained cause of death. Results: A total of 83 maternal sudden deaths and 4 949 890 live births occurred over the period studied, thus accounting for 16% of all maternal deaths ( n  = 510). Death was explained in 51 (61%) women and unexplained in 32 women (39%). Compared with women with unexplained death, women with explained death were more often found to have in‐hospital cardiac arrest (47% versus 12%, P  < 0.01), witnessed cardiac arrest (86% versus 62%, P  = 0.03) and in‐hospital death (82% versus 47%, P  < 0.01). Postmortem investigations such as autopsy and/or CT scan (65% versus 31%, P  < 0.01) were also more often carried out in women with explained death. The proportion of deaths for which the preventability factors could not be assessed was 58% among unexplained MSD and 7% among explained MSD. Conclusion: Maternal sudden death is a rare event but accounts for a high proportion of all maternal deaths. This highlights the importance of providing training in diagnostic and management strategy for care providers. Systematic postmortem investigations are required to help understand causes and improve practices.